Transcendental Unity of Apperception In Kant’sTheory of Knowledge - Hamid Fahmy Zarkasyi (TSAQAFAH, 2014)
This article aims at delineating Kant’s theory of understanding that integrate subject and object at the transcendent level. Transcendental here refers to the process of thinking in such a way that ‘transcends’ natural thinking. It is called transcendent for it occupied not so much with objects, but much about a metaphysical solution on how the object related to the subject. It starts with transcendental deduction by relating the objective with the subjective knowledge. Here he excludes transcendental deduction from the discussion of the empirical deduction. Afterward he differentiates the metaphysical deduction from transcendental deduction, in which he identifies transcendental deduction as the explanation of the way in which a priori concept can relate to object. The most important concept in Transcendental deduction is that of apperception. The analysis of this concept involve two abilities that later become two important steps: First ability of apprehending (reproducing and recognizing) knowledge of empirical truths. Second, ability of apprehending (reproducing and recognizing) knowledge of a non-empirical kind. Thus the general feature is the view that knowledge involve essentially the ability to judge (synthesize or combine) and the move from what is true empirically of our knowledge to what is true transcendentally. This is spontaneous act of mind and is called pure apperception or original apperception, while the principle that governs the unity of consciousness is entitled the Transcendental Unity of Apperception.